Evaluation of The Structural Teratment of The Tonusu Pendolo Road Section, Poso Regency - Muhammad Ali; Taslim Bahar; Arief Setiawan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The Tonusu–Pendolo Road Section in Poso Regency, Central Sulawesi, serves as a vital transportation corridor connecting Pamona Barat District and Pendolo District, spanning approximately 58.5 km. This road supports regional economic activities and traverses important ecological areas such as the Pamona Nature Reserve and the Bancea Natural Tourism Park. Field surveys indicate that the pavement is predominantly in light to severe damage, with defects including cracks, potholes, rutting, and surface depressions. The primary causes are excessive axle loads from heavy vehicles, inadequate drainage systems, and low subgrade strength. This study applies the Bina Marga Flexible Pavement Design Method to determine an optimal structural improvement strategy. Data collection included traffic volume surveys, subgrade CBR testing, and visual pavement inspections. The analysis revealed subgrade CBR values ranging from 5% to 8%, necessitating a thicker pavement structure to withstand projected traffic loads. The proposed design consists of a 4 cm Asphalt Concrete Wearing Course (AC-WC), 6 cm Asphalt Concrete Binder Course (AC-BC), 20 cm Aggregate Class A base course, and 20 cm Aggregate Class B subbase. Implementation of the proposed structure, combined with axle load control, drainage improvement, and periodic maintenance, is expected to extend service life, enhance safety, and improve overall road performance.